The Effect of E-Wallet Usage Intensity, Lifestyle, and Income on Personal Financial Management with Self-Control as a Moderating Variable among Private Employees in Pontianak - Maulidya Syafira; Heni Safitri; Dedi Hariyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of e-wallet usage intensity, lifestyle, and income on personal financial management, with self-control as a moderating variable among private employees in Pontianak City. The method used is quantitative with moderated regression analysis (Moderated Regression Analysis/MRA). The research sample consisted of 150 respondents selected using purposive sampling techniques. Data were collected through a questionnaire measured using a Likert scale and analyzed with SPSS version 25. The correlation coefficient test showed a strong relationship in the first model (R = 0.725) and a very strong relationship in the second model (R = 0.857) after considering self-control as a moderating variable. The coefficient of determination test (R²) in the first model shows that 52.5% of the variation in personal financial management is influenced by e-wallet usage intensity, lifestyle, and income, while in the second model, the R² value increased to 73.4%, indicating the role of self-control in moderating the relationship between these variables. Based on the Moderated Regression Analysis results, it can be concluded that self-control significantly moderates the effect of income on personal financial management, but does not moderate the effect of e-wallet usage intensity and lifestyle. The F test results show that e-wallet usage intensity, lifestyle, and income simultaneously have a significant effect on personal financial management. This study provides practical implications that to improve personal financial management among private employees in Pontianak City, attention needs to be given to the influence of e-wallet usage intensity, lifestyle, and income, by strengthening self-control to optimize financial management.